Me, My Colleagues, AI: using generative tools as support for users’ data collection, analysis, and organization in HCI classes - Silveira, Milene Selbach; Silva, Gabriel Fonseca (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: Students have widely used Generative Artificial Intelligence (AI) tools to assist them in their daily classroom activities and assignments (with or without the consent of their teachers). These tools are beneficial and, when used critically, can help students complete their tasks and better understand the various associated aspects. Objective: In this paper, we present an experience using AI tools to support the collection, analysis, and organization of user data in projects developed during a User Experience course in undergraduate computing programs. Methodology: The study involved two teachers and 99 students across three classes of the course. AI tools were integrated into project activities, and feedback was gathered from approximately half of the participants to assess their initial impressions. Results: The preliminary findings highlight the potential of generative AI tools to enhance student performance and learning in User Experience classes.